2022
DOI: 10.1021/acs.macromol.2c01759
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Polyelectrolyte Coacervation from a Molecularly Informed Field-Theoretic Model

Abstract: Understanding the phase behavior of polyelectrolyte coacervation is crucial for many applications, including consumer formulations, wet adhesives, processed food, and drug delivery. However, in most cases, modeling coacervation is not easily accessed by molecular simulation methods due to the long-range nature of electrostatic forces and the typically high molecular weights of the species involved. We present a modeling strategy to study complex coacervation leveraging the strengths of both particle simulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 79 publications
(149 reference statements)
0
6
0
Order By: Relevance
“…73 These analyses have been performed using experiment, 30,36,37,72−74 theory, 44,69,71 and simulation. 68,70,75 Capturing the multifaceted phase behavior that manifests in polyelectrolyte systems with five components presents a formidable challenge, given the considerable domains that can be investigated. A prevalent approach, as evidenced in the literature, 57,66,67 leverages 3D diagrams to encapsulate a broad spectrum of polyelectrolyte phase behavior.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…73 These analyses have been performed using experiment, 30,36,37,72−74 theory, 44,69,71 and simulation. 68,70,75 Capturing the multifaceted phase behavior that manifests in polyelectrolyte systems with five components presents a formidable challenge, given the considerable domains that can be investigated. A prevalent approach, as evidenced in the literature, 57,66,67 leverages 3D diagrams to encapsulate a broad spectrum of polyelectrolyte phase behavior.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Symmetric systems have proven easier to work with mathematically but fail to grasp the importance of asymmetry that appears in most real solutions. Asymmetric polyelectrolyte solutions have been investigated for differences in polymer concentration, , length, ,, charge density, ,, flexibility, and ion valency . These analyses have been performed using experiment, ,,, theory, ,, and simulation. ,, …”
Section: Introductionmentioning
confidence: 99%
“…The phase behavior in these systems results from a complex interplay between factors such as polymer chemistry, chain length, polymer concentration, charge ratio, temperature, pH, and ionic strength. ,,, The alteration in ionic strength of the media caused by the addition of salts (salt doping) can also alter the phase behavior. , It has been shown that increased salt concentration leads to phase transformation from solid precipitates to liquid coacervates and then to a homogeneous solution. ,, The mechanical responses of the complexes and their phase behavior with changing salt concentrations have been investigated by employing shear rheometry. ,, …”
Section: Introductionmentioning
confidence: 99%
“…Most of the investigations on the phase behavior of PECs in the literature involve a limited selection of synthetic polyelectrolytes. In contrast, studies on the phase change of natural polyelectrolyte complexes with the addition of salt are limited. , ,, Natural polyelectrolytes with high molecular weight, stiffer backbones, and long-range ionic interactions are expected to behave differently than synthetic polyelectrolytes. The formation of PECs from biopolymer pairs can be seen in several living systems responsible for various biological functions .…”
Section: Introductionmentioning
confidence: 99%
“…Strategies to control non-equilibrium behavior of synthetic PEC coacervates remain primitive, with the exception of ATP-fuelled time control of LLPS in specific chemistries. 14 In synthetic systems, the majority of coacervate research has aimed to characterize, model, and predict the complicated equilibrium phase behavior [15][16][17][18][19] and equilibrium rheology [20][21][22][23][24][25][26][27] of model coacervate-forming chemistries. Several pioneering studies established that titration order [28][29][30][31][32][33][34][35] and mixing efficiency 36 of polyanion, polycation, and salt can affect molecular-level structure.…”
Section: Introductionmentioning
confidence: 99%